FUNGSI PENGAWAS SEBAGAI PENDAMPING MADRASAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI MADRASAH TINGKAT MTS/MA KOTA MOJOKERTO - Afni, Maisya (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the function of madrasah supervisors as coach in enhancing teachers’ pedagogical competence at MTs/MA level madrasahs in Mojokerto City. The scope of the study includes the supervisory functions, the diversity of teachers’ pedagogical competence, and their implications for improving the quality of learning. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The findings reveal that although the functional position of supervisors has been formally integrated into the functional position of teachers, in practice, supervisors still hold significant authority in conducting supervision, mentoring, and coaching. Teachers’ pedagogical competence remains varied: some are capable of designing lesson plans and utilizing technology, while others require intensive guidance. The implications of supervisory mentoring are reflected through two main techniques, namely individual and group supervision, which proved effective in improving teachers’ pedagogical skills, lesson planning, and professional collaboration. Therefore, the continued function of supervisors as mentors is expected to strengthen learning quality and contribute to the overall improvement of madrasah education